Female Fertility Announcement: Do Female House Wrens (Troglodytes aedon) Adjust Singing Behavior Prior to Clutch Initiation? - Dunmon, Danielle (My University, 2020)
is fertile, few studies have explored whether females also adjust patterns of singing during early stages of breeding. For females, increased song output prior to clutch initiation and during egg laying may increase the likelihood of fertilization success. In this study, we test the hypothesis that female house wrens (Troglodytes aedon) that increase song output during their fertile period have higher fitness. We recorded the songs of females breeding in nest boxes, quantified song output, and defined reproductive success as the number of eggs laid and offspring fledged. Our study is an important step towards understanding the fitness causes and consequences of female singing behavior.